2006
DOI: 10.1007/s10658-006-9006-7
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, isolation and biological activity of phytotoxic metabolites produced in vitro by Sphaeropsis sapinea, pathogenic fungus of Pinus radiata

Abstract: Sphaeropsis sapinea was repeatedly isolated in Sardinia from symptomatic samples of the upper part of declining pine (Pinus radiata) plants. Observed symptoms mainly consisted of foliage chlorosis, drying of needles and cankers on branches. The S. sapinea strains were shown to produce phytotoxic metabolites in culture filtrates. Three metabolites were isolated for the first time from this fungus and identified by their spectroscopic and optical properties as R-())-mellein, (3R,4R)-4-hydroxymellein and (3R,4S)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
50
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 28 publications
9
50
0
1
Order By: Relevance
“…Above all, the most commonly reported bioactivity of mellein and its derivatives is their non-host-specific toxicity against plants. (R)-Mellein and hydroxymelleins have been isolated as phytotoxins of the apple and grapevine pathogen Botryosphaeria obtusa (53,65), the pine pathogen S. sapinea (57), the citrus pathogen Phoma tracheiphila (54), and the grapevine canker agent N. parvum (39). It has also been shown to induce phytotoxic symptoms on tomato cuttings when it is used at 100 g/ml (54) and causes necrosis on detached grape (Vitis vinifera) leaf at concentrations as low as 3 g/ml (65).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Above all, the most commonly reported bioactivity of mellein and its derivatives is their non-host-specific toxicity against plants. (R)-Mellein and hydroxymelleins have been isolated as phytotoxins of the apple and grapevine pathogen Botryosphaeria obtusa (53,65), the pine pathogen S. sapinea (57), the citrus pathogen Phoma tracheiphila (54), and the grapevine canker agent N. parvum (39). It has also been shown to induce phytotoxic symptoms on tomato cuttings when it is used at 100 g/ml (54) and causes necrosis on detached grape (Vitis vinifera) leaf at concentrations as low as 3 g/ml (65).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been observed that mellein slows the cell cycle, with the cell having an extended mitotic phase (68). Interestingly, the biological sources of (R)-mellein are overrepresented in fungal plant pathogens (39,53,54,57,65) and endophytes (51,52,58,59). Whether mellein plays a role in this plant-fungus interaction and why SN477 is strongly upregulated in planta are questions that warrant future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Mellein and its derivatives are not produced by esca-associated pathogens such as Pal, Pch and Fme (Djoukeng et al 2009). Mellein was the cause of frogeye leaf spot and black rot of apple (Venkatasubbaiah et al 1990 and1991) and was also produced by D. pinea, another Botryosphaeriaceae species, and caused the decline of Pinus radiata in Italy (Cabras et al 2006). However, mellein and its derivatives seem not to be produced exclusively by botryosphaeriaceous fungi, given that other studies have also associated these compounds with non-botryosphaeriaceous fungi such as the genera Phoma, Pezicula, Septoria, Sphaeropsis and Xylaria (Cabras et al 2006;Turner and Aldridge 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Dihydroisocoumarins have been isolated from several fungi, including species from the Aspergillus, Cercospora, Cryptosporiopsis, Hypoxylon, Phoma, and Xylaria genera (the list is not exhaustive) with phytotoxic, zootoxic and moderate antifungal activities (Turner and Aldridge, 1983;Cabras et al, 2006). Compounds 8, 9 and 10 were isolated from N. parvum (Evidente et al, 2010) with 7-hydroxymellein and 4,7-dihydroxymellein, which are phytotoxins produced by (D. seriata) B. obtusa from grapevine (Djoukeng et al, 2009).…”
Section: Phytotoxic Activitymentioning
confidence: 99%